Uji Performa Kendaraan Motor Listrik Transmisi Chain dan Van Belt - Wahyu Isti Nugroho; Ahmad Hamim Su’udy; Muhammad Showi Nailul Ulum; Slamet Priyoatmojo; Atikah Ayu Janitra; Ahmad Mamba'udin (Politeknik Negeri Semarang, 2026)
The purpose of this study is to compare the performance of chain and belt timing transmission on a 2 kW electric motorcycle used in an electric conversion vehicle. This research is based on the popularity of electric motorcycles as an environmentally friendly transportation alternative and the need for more efficient transmission systems to improve vehicle efficiency. Although electric motors are highly efficient, it is important to choose the right transmission system to transmit power to the wheels. This study analyzes the effect of transmission type on the torque and power generated using dynotest testing to compare the performance of each. For this study, the transmission system was designed with a chain and timing belt with the same ratio. Then, using a dynotest, tests were conducted at various rotation speeds. The test results showed that the chain and timing belt produced greater torque and power at certain ratios, and the chain produced lower torque and power at other ratios. This study found that the transmission ratio affects the efficiency of torque and power transfer in chain and timing belt transmissions. By identifying the components that affect the performance of the transmission system, this study provides important information for the development of electric motorcycles. Ultimately, this will help electric vehicles become more efficient and reliable.